100 years of architectural drawing : 1900-2000 - Bingham, Neil (Laurence King Publishing Ltd, 2013)
Brings together 300 of the architectural drawings from the last century by the world's most prestigious architects, creating both a history of the genre and a survey of twentieth-century architecture. This book is divided into five chronological sections that are prefaced by short essays that highlight the trends and styles of that period.